Assessing the impact of institutional quality and environmental depletion on sustainable development practices in Nigeria (SBS Journal of Applied Business Research, 2025)
The challenge of determining the drivers of sustainable development in Nigeria has emerged as a key research topic. Consequently, there is an urgent need to clarify these ambiguous initial assumptions and examine their impact on the sustainable development trajectory in Nigeria. This study utilized an extensive dataset from 1996 to 2023, extracted from the World Bank database, to explore the complex issues surrounding sustainable development in Nigeria, particularly aiming to provide empirical validation through the institutional quality- environmental degradation framework. This approach provides deeper understanding of the uncertain relationships within the subject. The ARDL cointegration technique was employed to analyze the data. The results indicated that sustainable development in Nigeria is obstructed by poor institutional quality and environmental harm. Moreover, the findings suggest that environmental degradation exerts a crowd-out effect from the first-period to the fourth-period lag, while institutional quality from the first-period to the third-period lags negatively and significantly affects sustainable development at a 5% significance level respectively. In essence, development in Nigeria heavily depends on prior environmental conditions and the influence of institutional quality. As such, short-term policy initiatives should prioritize creating conditions for sustainable development through strong institutional quality and environmental sustainability.